2016
DOI: 10.1159/000447270
|View full text |Cite
|
Sign up to set email alerts
|

Higher Fluorosis Severity Makes Enamel Less Resistant to Demineralization

Abstract: Fluorotic teeth could either be more resistant or more susceptible to the caries process than sound ones due to their higher enamel fluoride concentration and higher porosity (subsurface hypomineralization), respectively; however, there is no consensus on this subject. In this study, a total of 49 human unerupted third molars presenting Thylstrup and Fejerskov (TF) fluorosis scores 0-4 were used. Two enamel slabs were obtained from each tooth. The rest of the tooth crown was powdered, and the enamel was separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Its clinical appearance varies from white diffuse and irregular lines in mild cases to loss of structure and marked discoloration in the more severe forms [ 1 ]. Teeth with DF higher severity score show decreased resistance to demineralization, compared to sound enamel on lab studies or natural teeth [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its clinical appearance varies from white diffuse and irregular lines in mild cases to loss of structure and marked discoloration in the more severe forms [ 1 ]. Teeth with DF higher severity score show decreased resistance to demineralization, compared to sound enamel on lab studies or natural teeth [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…From one individual to another, the age, the living location, or the amount of fluorine available during tooth formation are causes for fluorine concentration variation. Moreover, in the same individual, the type of tooth (canine, incisor, premolar or molar), the tooth surface (labial, distal, lingual or mesial), the tooth region (occlusal, middle, cervical), and the depth of measurement can present different fluorine concentrations …”
Section: Resultsmentioning
confidence: 99%
“…When faced with a cariogenic challenge, it is the subsurface apatite crystals that are dissolved, consequently causing a subsurface lesion [ 14 ]. Accordingly, it can be reasonably concluded that a fluorotic tooth displaying higher clinical severity represents a wider mineral area to be dissolved by acids and the permeability of acid through enamel might be elevated [ 4 ]. In more clinically severe forms of DF post-eruptive damage happens, revealing less caries-resistant subsurface (see descriptions below).…”
Section: Dental Fluorosis Classificationmentioning
confidence: 99%
“…This porous characteristic is demonstrated by clinical features ranging from enamel opacities, discoloration, or stains to structural defects (pits, cracks, and fissures) [ 1 , 2 ]. However, despite its intimate relationship with fluoride, which is widely recognized as “the cornerstone of dental caries reduction” [ 3 ], the enamel caries susceptibility of DF has remained ambiguous [ 4 ]. Epidemiological surveys have demonstrated contradictory conclusions.…”
Section: Introductionmentioning
confidence: 99%